Exploring the Efficacy of Collaborative Professional Learning Communities in Enhancing ESL Teaching Practices - Ramila Ahmad; Shah Faisal; Haleema Rouf (University of Chitral Journal of Linguistics and Literature, 2023)
This study explores the impact of Collaborative Professional Learning Communities (CPLCs) on ESL teaching practices in the context of Lahore, Pakistan. Eighteen ESL teachers participated in semi-structured interviews, providing insights into the influence of CPLCs on pedagogical strategies, cultural relevance, professional growth, and student outcomes. Results indicate that CPLCs play a pivotal role in enhancing ESL teaching practices by facilitating the exchange of innovative ideas, addressing cultural nuances, and fostering professional support. Notably, the study identifies a positive correlation between CPLC participation and improved student learning outcomes. The findings contribute to the broader discourse on the transformative potential of collaborative communities in ESL education, emphasizing the need for sustained efforts to overcome implementation challenges. As educators seek dynamic approaches to meet the diverse linguistic and cultural needs of ESL learners, CPLCs emerge as integral hubs for fostering collaborative learning environments that positively impact both educators and students in the dynamic educational landscape of Lahore, Pakistan.